Sosialisasi Program Diklat Pemberdayaan Masyarakat (DPM) Bagi Masyarakat Nelayan dan Taruna Pelayaran - Suganjar Suganjar; Asep Yedi Heryadi; Heru Widada; Zaky Maulana; Asmul Khairi (Fakultas Teknik Universitas Cenderawasih, 2023)
The aim of implementing community empowerment training is to reduce unemployment and increase the competency of training participants to produce professional ship crew human resources as a means of economic equality throughout Indonesia. Types of community empowerment training provided to communities in need include Basic Safety Training (BST), Security Awareness Training (SAT), Advanced Fire Fighting (AFF), SKK 30 miles on deck, SKK 30 miles on engines, SKK 60 miles on deck, SKK 60 mil on engines, and basic safety for traditional boat. The socialization of community empowerment training is divided into several stages, including the preparation stage, the implementation stage, and the evaluation stage. The implementation of socialization is carried out using the method of direction and discussion regarding the instructor's concepts and abilities, the number of participants, and implementation time in the implementation of training. Community empowerment training, which is carried out free of charge, can provide opportunities for underprivileged communities to develop skills and knowledge regarding competencies in the maritime sector, increasing the capacity and capability of fishing communities.